2014
DOI: 10.1002/cncr.29175
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of oral abexinostat, a histone deacetylase inhibitor, in combination with doxorubicin in patients with metastatic sarcoma

Abstract: Introduction Several inhibitors of histone deacetylase have been shown to enhance chemotherapy induced apoptosis and reduce sarcoma tumor volume in preclinical models. We sought to determine the MTD, PK/PD, safety and toxicity of the histone deacetylase inhibitor (HDACi) abexinostat (PCI-24781) when administered with doxorubicin in patients with metastatic sarcomas. Methods Participants were enrolled in a standard 3+3 dose escalation phase I study design. Abexinostat was administered on days 1–5 with 75 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 20 publications
2
36
1
Order By: Relevance
“…More importantly, the maximum tolerated dose of abexinostat and doxorubicin exceeded doses for maximal histone acetylation, so that the effectiveness of this combination would not be limited by inadequate dosing. Clinical benefit of this combination resulted in 7 out of 17 evaluable participants maintained stable disease for at least 5 cycles of chemotherapy 113 . Another study evaluated the response rate of belinostat in combination with doxorubicin for patients with soft tissue sarcoma.…”
Section: Clinical Trials Of Hdis In Sarcomamentioning
confidence: 99%
“…More importantly, the maximum tolerated dose of abexinostat and doxorubicin exceeded doses for maximal histone acetylation, so that the effectiveness of this combination would not be limited by inadequate dosing. Clinical benefit of this combination resulted in 7 out of 17 evaluable participants maintained stable disease for at least 5 cycles of chemotherapy 113 . Another study evaluated the response rate of belinostat in combination with doxorubicin for patients with soft tissue sarcoma.…”
Section: Clinical Trials Of Hdis In Sarcomamentioning
confidence: 99%
“…[3] In the meantime, more than ten hydroxamate-based pan-HDACIs are under clinical investigation for the treatment of various cancers (Figure 1). [4] Outside oncology, the targeting of specific HDAC isoforms is being pursued as a promising therapeutic strategy for neurological disorders, [5] based on the finding that several selective HDACIs bearing hydroxamate groups exhibit neuroprotective properties and improve cognition and motor activity, as well as other behaviors in animal models of depression, [6] Alzheimer’s disease (AD), [7] Huntington’s disease (HD), [8] Charcot– Marie–Tooth disease (CMT), etc. [9] The potential utility of HDAC inhibitors appears to be tremendous, but further translation of these ideas to the clinic will ultimately require the design of potent, isozyme-selective, and drug-like molecules that have minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients had Ewing’s sarcoma, but the drug appeared to be well tolerated 123. Another Phase I study again showed tolerability of abexinostat in combination with doxorubicin 124. The combination of vorinostat with bortezomib (a proteasome inhibitor) was tested in a Phase I study of patients with advanced solid tumors and appeared to have a favorable side effect profile, with some clinical responses 125.…”
Section: Drugs That Target Other Pathwaysmentioning
confidence: 99%